2020
DOI: 10.1136/bmjopen-2020-039231
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of wheat with zinc for eliminating deficiency in Pakistan: study protocol for a cluster-randomised, double-blind, controlled effectiveness study (BIZIFED2)

Abstract: IntroductionMicronutrient deficiencies, commonly referred to as ‘hidden hunger’, affect more than two billion people worldwide, with zinc and iron-deficiency frequently reported. The aim of this study is to examine the impact of consuming zinc biofortified flour (Zincol-2016) on biochemical and functional measures of status in adolescent girls and children living in a low-resource setting in Pakistan.Methods and analysisWe are conducting a pragmatic, cluster-randomised, double-blind, controlled trial. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Efficacy trials may thus provide proof of concept; however, effectiveness trials are necessary to demonstrate acceptability, impact and scalability in real-world situations. We are conducting a programme of research, known as BiZiFED, to evaluate the potential for a HarvestPlus produced zinc-biofortified wheat variety, Zincol-2016, to improve zinc status in women of reproductive age and adolescent girls and infants in Pakistan (42,47) . In the first phase of this programme, a study was conducted to explore the performance of Zincol-2016 under different soil conditions and fertilizer regimens.…”
Section: Biofortificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Efficacy trials may thus provide proof of concept; however, effectiveness trials are necessary to demonstrate acceptability, impact and scalability in real-world situations. We are conducting a programme of research, known as BiZiFED, to evaluate the potential for a HarvestPlus produced zinc-biofortified wheat variety, Zincol-2016, to improve zinc status in women of reproductive age and adolescent girls and infants in Pakistan (42,47) . In the first phase of this programme, a study was conducted to explore the performance of Zincol-2016 under different soil conditions and fertilizer regimens.…”
Section: Biofortificationmentioning
confidence: 99%
“…Whilst more information is needed regarding the bioavailability of the zinc from the grain, initial studies indicate that the phytate content (main inhibitor of zinc absorption) of the Zincol-2016 grain is equivalent to that of standard varieties. The current phase of the research programme involves a double-blind cluster randomised trial of 500 households who are receiving either starch milled from Zincol-2016 wheat grain grown by local farmers, or a control non-biofortified variety (Galaxy), for a period of 6 months (42) . The cluster randomised trial is currently underway and the outcome measures include biomarkers of zinc status, anthropometry, and incidence and duration of diarrhoea and upper respiratory tract infections in adolescent girls and infants.…”
Section: Biofortificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations living in rural socio-economically deprived communities may be at higher risk of micronutrient deficiencies as they typically have low diet diversity and a high prevalence household food insecurity [7]. We have found that approximately 30% of women of reproductive age living in the brick kiln areas around Peshawar had plasma zinc concentrations that fall below the cut-off value of 660 µg/L for adequacy [8]. Effective actions to eliminate hidden hunger among the most vulnerable groups are required to achieve the Sustainable Development Goal 2 of Zero hunger by 2030 [9].…”
Section: Introductionmentioning
confidence: 85%
“…By 2050, due to the increase in the world population, to avoid hunger, food production must significantly increase [1]. In addition, to ensure safety, food also must have high quality, specifically at a prophylactic level, providing the necessary nutrients, since it is expected that their deficiency might affect the health of more than two billion people worldwide [2,3]. In this context, some alternatives are being suggested, namely, agronomic Biol.…”
Section: Introductionmentioning
confidence: 99%